CREB participates in the IGF‐I‐stimulation cyclin D1 transcription. Issue 8 (24th June 2013) - Yan, Yun; Li, Xiaoyu; Kover, Karen; Clements, Mark; Ye, Ping
ABSTRACT IGF‐I stimulates proliferation and cell cycle progression in progenitor cells of a number of neural cell types, including neuronal and glial progenitors. The precise mechanisms of this regulation, however, have not been fully defined. To elucidate the mechanism of IGF‐I actions on neural cell proliferation, we utilized a rat oligodendroglial cell line (OL‐1) and primary oligodendrocyte precursors (OPC) and studied IGF‐I regulation of cyclin D1 expression and its promoter activity, because cyclin D1 is critical to the promotion of cell proliferation and cell cycle progression. Transient transfection of a reporter driven by the rat cyclin D1 promoter showed that IGF‐I stimulates cyclin D1 promoter activity. Furthermore, 5′‐end deletions and mutation analysis of this promoter revealed that a cAMP response element (CRE) within −174 base pair (bp) upstream of the transcription start site is crucial to the IGF‐induced increase in cyclin D1 transcription. Consistently, Western immunoblot analysis demonstrated that IGF‐I induced CREB (CRE binding protein) phosphorylation, while ablation of CREB expression with small interfering RNAs (siRNA) blocked IGF‐I actions on cyclin D1 mRNA expression and cell proliferation. Additionally, IGF‐I‐stimulated CREB phosphorylation was blunted by the MAP kinase inhibitor, PD98059, but not by the PI3 kinase inhibitor, wortmannin. ChIP assays revealed that IGF‐1 increased the association of CREB with the cyclin D1 promoter. Taken together, our data indicate that IGF‐I upregulates cyclin D1 transcription partially by inducing CREB phosphorylation through the ERK‐MAP kinase pathway, and thus increasing its recruitment to the cyclin D1 promoter. These results provide an important mechanism of IGF‐I‐induced glial cell growth and proliferation. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 73: 559–570, 2013